On the importance of temporal floc size statistics and yield strength for population balance equation flocculation model. (15th April 2023) - Penaloza-Giraldo, Jorge A.; Hsu, Tian-Jian; Manning, Andrew J.; Ye, Leiping; Vowinckel, Bernhard; Meiburg, Eckart
Highlights: Median floc size is insufficient for calibrating PBE flocculation model. A complete model calibration reveals a lower floc yield strength in larger flocs. Incorporating a variable floc yield strength greatly improves the model prediction. Abstract: Many aquatic environments contain cohesive sediments that flocculate and create flocs with a wide range of sizes. The Population Balance Equation (PBE) flocculation model is designed to predict the time-dependent floc size distribution and should be more complete than models based on median floc size. However, a PBE flocculation model includes many empirical parameters to represent important physical, chemical, and biological processes. We report a systematic investigation of key model parameters of the open-source PBE-based size class flocculation model FLOCMOD (Verney, Lafite, Claude Brun-Cottan and Le Hir, 2011) using the measured temporal floc size statistics reported by Keyvani and Strom (2014) at a constant turbulent shear rate S . Results show that the median floc size d 50, in terms of both the equilibrium floc size and the initial floc growth, is insufficient to constrain the model parameters. A comprehensive error analysis shows that the model is capable of predicting three floc size statistics d 16, d 50 and d 84, which also reveals a clear trend that the best calibrated fragmentation rate (inverse of floc yield strength) is proportional to the floc size statistics considered. Motivated by this finding, the importance of floc yield strength is demonstrated in the predicted temporal evolution of floc size by modeling the floc yield strength as microflocs and macroflocs giving two corresponding fragmentation rates. The model shows a significantly improved agreement in matching the measured floc size statistics.